Inulin-based nanocomposite hydrogel, preparation method and application thereof

CN122874602APending Publication Date: 2026-10-09THE FIRST AFFILIATED HOSPITAL OF BENGBU MEDICAL COLLEGE
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202611304902.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-26
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

然而,上述策略存在以下固有缺陷:第一,大分子稳定剂通常具有较宽的分子量分布,且可能引入不可控的基质效应,影响药物递送系统的批次间重现性;第二,尽管这些大分子具有良好的生物相容性,但其缺乏内在的抗肿瘤生物活性,无法增强联合治疗的整体效果;第三,后负载药物策略中药物与纳米颗粒的结合不牢固,循环过程中易发生药物提前泄漏,且药物载量有限

Benefits of technology

[0022]本发明首次提出”药物作为稳定剂”的纳米颗粒合成策略,利用结构明确的小分子化疗药物米托蒽醌直接作为Cu2Se纳米颗粒的稳定剂,无需使用壳聚糖、BSA等惰性大分子稳定剂。米托蒽醌分子中的蒽醌环和侧链氨基可通过配位相互作用结合于硒化亚铜纳米颗粒表面,既有效抑制了纳米颗粒在生理环境中的聚集和沉淀,又直接将化疗功能整合至纳米颗粒核心,简化了纳米结构,避免了惰性大分子稳定剂带来的分子量分布宽、批次重现性差、基质效应不可控等问题,同时克服了传统大分子稳定剂缺乏内在抗肿瘤活性而无法增强联合治疗效果的缺陷。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The application discloses a kind of inulin-based nanocomposite hydrogel, preparation method and application, belong to the field of biomedical materials and nano medicine.It includes inulin hydrogel matrix and mitoxantrone-copper selenide nanocomposite particles dispersed therein;Nanocomposite particles are made by mitoxantrone as stabilizer to stabilize copper selenide nanoparticles, and mitoxantrone is combined on the surface of nanoparticles in coordination form;Inulin hydrogel matrix is formed by temperature-sensitive sol-gel transition from inulin aqueous solution.This hydrogel does not need inert macromolecular stabilizer, and has uniform and stable particle size, tumor microenvironment-responsive release and near-infrared photothermal conversion performance;Under 808nm laser irradiation, photothermal effect triggers gel network partial dissociation, promotes nanocomposite particles to penetrate into deep tumor and release mitoxantrone, realizes chemotherapy-photothermal synergistic treatment, and the tumor inhibition rate of H22 tumor-bearing mice reaches 95.4%, with good biocompatibility, which can be used for solid tumor synergistic treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the fields of biomedical materials and nanomedicine, and in particular to an inulin-based nanocomposite hydrogel, its preparation method and its application. More specifically, it relates to a nanocomposite hydrogel formed by preparing mitoxantrone-cuprous selenide nanocomposite particles using mitoxantrone as a stabilizer and loading them into an inulin thermosensitive hydrogel, and the application of this nanocomposite hydrogel in tumor chemotherapy-photothermal synergistic therapy. Background Technology

[0002] Malignant tumors remain one of the most serious challenges facing global public health. Currently used clinical treatments such as chemotherapy and surgery often suffer from significant systemic toxicity, insufficient drug retention at the tumor site, and a high risk of postoperative recurrence. In recent years, photothermal therapy (PTT) based on near-infrared (NIR) responsive materials has emerged as a promising non-invasive cancer treatment method. PTT converts near-infrared light energy into localized heat using a photothermal converter, inducing thermal ablation of tumor cells while minimizing damage to surrounding healthy tissues. However, PTT alone often fails to completely eradicate tumors, easily leading to recurrence and metastasis. Therefore, combining photothermal agents with chemotherapeutic drugs through a rational delivery system to achieve chemo-photothermal combined therapy has become an important direction in anti-tumor drug delivery research.

[0003] Among transition metal-based semiconductor photothermal agents, cuprous selenide (Cu2Se) nanoparticles exhibit strong near-infrared absorption and excellent photothermal conversion efficiency, making them an ideal candidate material for synergistic tumor therapy. However, Cu2Se nanoparticles are inherently unstable in physiological environments, readily agglomerating and precipitating, a defect that significantly reduces their bioavailability and therapeutic efficacy. To address the aforementioned issues, existing technologies typically employ two strategies: First, natural macromolecules such as chitosan, carboxymethyl chitosan, gellan gum, or bovine serum albumin (BSA) are introduced as stabilizers during the synthesis of Cu2Se nanoparticles to ensure the colloidal stability of the nanoparticles. For example, Chen et al. reported the preparation of Cu2Se nanoparticles stabilized with BSA (BSA-Cu2SeNPs), which were further loaded with the anthracycline chemotherapy drug doxorubicin (DOX), achieving excessive reactive oxygen species generation and synergistic therapeutic effects under near-infrared laser irradiation (Chenetal., Colloids and Surfaces B: Biointerfaces, 2018). Second, surface-modified Cu2Se nanoparticles are synthesized first, and then chemotherapy drugs are loaded via physical adsorption or chemical coupling. However, the above strategies have the following inherent drawbacks: First, macromolecular stabilizers usually have a wide molecular weight distribution and may introduce uncontrollable matrix effects, affecting the batch-to-batch reproducibility of the drug delivery system; Second, although these macromolecules have good biocompatibility, they lack intrinsic antitumor biological activity and cannot enhance the overall effect of combination therapy; Third, in the post-loaded drug strategy, the binding between the drug and nanoparticles is not strong, and premature drug leakage is prone to occur during circulation, and the drug loading capacity is limited.

[0004] Regarding hydrogel carriers, Chinese patent CN116785234A discloses a drug-loaded nanocomposite hydrogel, its preparation method, and its application. It consists of internal drug-loaded hollow manganese dioxide nanoparticles and an externally modified inulin hydrogel "shell." Targeted drug delivery to the colon is achieved through the synergistic effect of the inulin hydrogel, hollow manganese dioxide nanoparticles, and the drug. However, the inulin hydrogel in this design is only used as a surface modification layer for colonic retention, and the nanoparticles are synthesized separately and then physically combined with the inulin hydrogel. It does not involve the technical concept of using chemotherapy drugs as nanoparticle stabilizers, nor is its application in photothermal therapy observed. Chinese patent CN119454750B discloses a magnesium boride nanosheet / inulin composite hydrogel and its application in treating inflammatory bowel disease and comorbid mental illness. In this design, the inulin hydrogel acts as a drug carrier, but the loaded magnesium boride nanosheets are primarily used for intestinal anti-inflammatory treatment and are unrelated to tumor photothermal therapy. Furthermore, Chinese patent CN112972366A discloses an injectable photothermal chemotherapy-sensitizing drug-loaded hydrogel, which uses a thermosensitive synthetic phospholipid hydrogel combined with drug-loaded nanomicelles to achieve a combination of photothermal and chemotherapy. However, the photothermal agent used is a traditional photothermal material such as polydopamine-encapsulated gold nanoparticles, and the hydrogel matrix is ​​a synthetic phospholipid, not a natural polysaccharide inulin hydrogel. No scheme using chemotherapy drugs as nanoparticle stabilizers has been found. Chinese patent CN111728938A discloses an injectable hydrogel system combining chemotherapy and photothermal therapy, but it also uses a synthetic polymer hydrogel matrix, and the drug and photothermal agent are loaded separately.

[0005] Regarding cuprous selenide nanomaterials, Chinese patent CN114870013A discloses a hollow copper selenide composite spherical nanoparticle and its preparation method and application; Chinese patent CN114533868A discloses a gold composite copper selenide nanoparticle and its preparation method and application; and Chinese patent CN120229691A discloses a preparation method of a copper selenide nanoenzyme and its photothermal application. All of the above patents involve the preparation and photothermal application of copper selenide nanoparticles, but they all adopt conventional stabilization strategies such as surfactants, template agents, or noble metal composites, and none of them involve technical solutions that use structurally well-defined small molecule chemotherapy drugs as stabilizers to directly participate in the synthesis of nanoparticles. Regarding mitoxantrone nanoparticles, Chinese patent CN109125272A discloses a method for preparing mitoxantrone nanoparticles loaded with fluorinated graphene as a carrier, and Chinese patent CN102579355A discloses a mitoxantrone nano-calcium phosphate formulation and its preparation method. In the above schemes, mitoxantrone is the loaded guest drug, rather than a stabilizer for nanoparticle synthesis.

[0006] Further analysis of existing technologies reveals that the aforementioned shortcomings are inherently interconnected: On the one hand, while the macromolecular stabilizer strategy solves the colloidal stability problem of nanoparticles, it introduces new uncontrollable factors, and the macromolecular stabilizer itself does not possess therapeutic function, belonging to "inert stability." On the other hand, even with a post-loaded drug strategy, the lack of strong binding force between the drug and nanoparticles leads to premature drug release during blood circulation and tumor tissue penetration, resulting in decreased efficacy and increased systemic toxicity. More critically, in existing technologies, the relationship between photothermal agents, chemotherapeutic drugs, and the hydrogel matrix is ​​often a simple physical mixture, lacking a synergistic response design: the photothermal effect is usually only used to directly kill tumor cells, rather than being utilized to regulate the structure of the hydrogel matrix (such as triggering gel network dissociation) to promote drug delivery to deeper tumors; chemotherapeutic drugs are usually simply embedded in the gel matrix, and due to the dense gel network, diffusion is slow, making it difficult to achieve deep penetration into tumor tissue, resulting in incomplete treatment and a high recurrence rate. In addition, existing hydrogel carriers are mostly made of synthetic polymers (such as polyphospholipids, poloxamer, polylactic acid-glycolic acid copolymers, etc.) or modified by chemical cross-linking. The preparation process is complex and may introduce toxic cross-linking agents, posing potential risks to biocompatibility and biodegradability. Although natural polysaccharide hydrogels (such as sodium alginate and chitosan hydrogels) have good biocompatibility, they mostly require ionic or chemical cross-linking to form a gel, which is subject to harsh process conditions, and stable composites with inorganic photothermal nanoparticles are rare.

[0007] It is particularly noteworthy that those skilled in the art, when addressing the colloidal stability of Cu2Se nanoparticles, exhibit a clear technological path dependency: stabilizing nanoparticles through steric hindrance or electrostatic interactions using macromolecules (BSA, chitosan, carboxymethyl chitosan, gellan gum, polyethylene glycol, etc.). Macromolecular stabilizers, capable of forming thick steric hindrance layers, are the mainstream choice in nanoparticle stabilization. Small molecule stabilizers (especially small organic molecules), due to their small molecular size and weak steric hindrance, are generally considered ineffective at stabilizing inorganic nanoparticles. Therefore, those skilled in the art have no incentive to abandon the mature macromolecular stabilization strategy in favor of small molecule chemotherapeutic drugs as stabilizers. Even more unexpectedly, the small molecule chemotherapeutic drug mitoxantrone can not only stabilize Cu2Se nanoparticles but also form coordination bonds with the surface of cuprous selenide, resulting in a robust loading. Furthermore, this coordination bond can be competitively disrupted in the high glutathione concentration of the tumor microenvironment, leading to responsive drug release. Simultaneously, mitoxantrone itself, as a clinically approved chemotherapeutic drug, possesses inherent antitumor activity. The integrated realization of the aforementioned triple functions of "stabilizer, drug carrier, and chemotherapeutic drug" on the small molecule mitoxantrone is neither explicitly taught nor technically inspired in the existing technology, and thus constitutes a non-obvious inventive concept. Similarly, no existing literature or patent discloses a technical solution for using structurally well-defined small molecule chemotherapeutic drugs such as mitoxantrone as stabilizers in the synthesis of Cu2Se nanoparticles and loading them into inulin thermosensitive hydrogels to construct injectable nanocomposite hydrogels for tumor chemotherapy-photothermal synergistic therapy. Therefore, developing a nanoparticle stabilization strategy based on structurally well-defined small molecules with intrinsic therapeutic activity, and combining it with a hydrogel delivery system to achieve a technical solution that integrates "stabilizer function and therapeutic function, and couples photothermal effect with gel dissociation response," is both a key scientific challenge urgently needing to be addressed in this field and an important clinical translational requirement. Summary of the Invention

[0008] To address the shortcomings of existing technologies, the present invention aims to provide an inulin-based nanocomposite hydrogel, its preparation method, and its applications. The core concept of the invention lies in using mitoxantrone (MIT), a structurally well-defined small-molecule chemotherapy drug, directly as a stabilizer in the synthesis of Cu2Se nanoparticles. During the synthesis process, the chemotherapy function is integrated into the core of the nanoparticles without the need for any inert macromolecular stabilizers. Subsequently, the obtained mitoxantrone-cuprous selenide nanocomposite particles are loaded into an inulin thermosensitive hydrogel to construct an injectable nanocomposite hydrogel (NP@Gel), achieving a synergistic effect of chemotherapy and photothermal therapy.

[0009] The above-mentioned objective of this invention is achieved through the following technical solutions:

[0010] This invention relates to three aspects of technical solutions: First, it provides an inulin-based nanocomposite hydrogel product; second, it provides the mitoxantrone-cuprous selenide nanocomposite particles and a method for preparing the inulin-based nanocomposite hydrogel; third, it provides the application of the inulin-based nanocomposite hydrogel in tumor chemotherapy-photothermal synergistic therapy.

[0011] This invention provides an inulin-based nanocomposite hydrogel, comprising an inulin hydrogel matrix and mitoxantrone-cuprous selenide nanocomposite particles dispersed in the inulin hydrogel matrix; the mitoxantrone-cuprous selenide nanocomposite particles are formed by in-situ stabilization of cuprous selenide nanoparticles with mitoxantrone as a stabilizer, and the mitoxantrone is coordinated to the surface of the cuprous selenide nanoparticles; the inulin hydrogel matrix is ​​formed by thermosensitive sol-gel transformation of inulin aqueous solution, and the mitoxantrone-cuprous selenide nanocomposite particles are uniformly dispersed in the inulin hydrogel matrix; the inulin-based nanocomposite hydrogel can generate photothermal conversion under near-infrared light irradiation and can release mitoxantrone in response to the tumor microenvironment.

[0012] Furthermore, in the mitoxantrone-cuprous selenide nanocomposite particles, the molar ratio of mitoxantrone to selenium is 1:6 to 1:2; the average particle size of the mitoxantrone-cuprous selenide nanocomposite particles is 50-100 nm; and the polydispersity index of the mitoxantrone-cuprous selenide nanocomposite particles is not higher than 0.4. As a specific embodiment, the molar ratio of mitoxantrone to selenium is 1:4, the average particle size is 50-90 nm, and the polydispersity index is not higher than 0.35.

[0013] Furthermore, the concentration of inulin in the inulin aqueous solution is 400-600 mg / mL; the gelation time of the inulin-based nanocomposite hydrogel is 0.52 h. As a specific embodiment, the inulin concentration is 500 mg / mL, and the gelation time is 1 h.

[0014] The present invention also provides a method for preparing mitoxantrone-cuprous selenide nanocomposite particles, comprising the following steps: reducing sodium selenite with ascorbic acid to obtain selenium nanoparticles; adding mitoxantrone solution to a suspension of the selenium nanoparticles to obtain selenium nanoparticles loaded with mitoxantrone; then adding copper chloride solution to convert the selenium nanoparticles into cuprous selenide nanoparticles, and purifying by dialysis to obtain the mitoxantrone-cuprous selenide nanocomposite particles.

[0015] This invention also provides a method for preparing inulin-based nanocomposite hydrogels, comprising the following steps: dissolving inulin in water and stirring at 30-40°C to obtain an inulin precursor solution; dispersing mitoxantrone-cuprous selenide nanocomposite particles obtained by the above preparation method in the inulin precursor solution, wherein the concentration of the mitoxantrone-cuprous selenide nanocomposite particles is 50-500 μg / mL; and then cooling and allowing the system to stand at 0-10°C to allow the system to undergo a thermosensitive sol-gel transition, thereby forming the inulin-based nanocomposite hydrogel in situ.

[0016] Furthermore, the inulin-based nanocomposite hydrogel can responsively release mitoxantrone under simulated tumor microenvironment conditions: under pH 5.0~6.0 and containing 520mM glutathione, the cumulative release rate of mitoxantrone is 60%~75% within 2 hours and 70%~80% within 24 hours; and under near-infrared light irradiation, the inulin hydrogel matrix undergoes partial dissociation, promoting the release and penetration of the mitoxantrone-cuprous selenide nanocomposite particles.

[0017] Furthermore, the inulin-based nanocomposite hydrogel, after being irradiated with an 808nm near-infrared laser at a power density of 0.5~2W / cm² for 5 minutes, exhibits a temperature rise to 45~65℃. In a specific embodiment, after irradiation with an 808nm near-infrared laser at a power density of 1W / cm² for 5 minutes, the temperature rises to 55~60℃.

[0018] The present invention also provides the application of the above-mentioned inulin-based nanocomposite hydrogel in the preparation of drugs or formulations for tumor chemotherapy-photothermal synergistic therapy.

[0019] Furthermore, the drug or preparation is administered via intratumoral or peritumoral injection, forming a gel reservoir in situ at the injection site. After administration, the tumor site is irradiated with a near-infrared laser, which, while achieving photothermal ablation, triggers partial dissociation of the inulin-based nanocomposite hydrogel, promoting the penetration of the mitoxantrone-cuprous selenide nanocomposite particles into the deeper layers of the tumor and releasing mitoxantrone, thus achieving synergistic effects of chemotherapy and photothermal therapy. The near-infrared laser is an 808nm laser with a power density of 0.5~2W / cm² and an irradiation time of 3~10min.

[0020] Furthermore, the tumor is a solid tumor, including liver cancer, colorectal cancer, breast cancer, cervical cancer, melanoma, or lung cancer; the inulin-based nanocomposite hydrogel exhibits an inhibition rate of no less than 90% on tumor growth. As a specific embodiment, the tumor growth inhibition rate in H22 tumor-bearing mice is 95.4%.

[0021] In summary, compared with the prior art, the present invention has at least one of the following beneficial technical effects:

[0022] This invention proposes for the first time a nanoparticle synthesis strategy using a drug as a stabilizer. It utilizes the structurally well-defined small-molecule chemotherapeutic drug mitoxantrone directly as a stabilizer for Cu2Se nanoparticles, eliminating the need for inert macromolecular stabilizers such as chitosan and BSA. The anthraquinone ring and side-chain amino groups in the mitoxantrone molecule can bind to the surface of cuprous selenide nanoparticles through coordination interactions. This effectively inhibits the aggregation and precipitation of nanoparticles in the physiological environment and directly integrates the chemotherapeutic function into the nanoparticle core, simplifying the nanostructure. It avoids the problems associated with inert macromolecular stabilizers, such as wide molecular weight distribution, poor batch-to-batch reproducibility, and uncontrollable matrix effects. Furthermore, it overcomes the shortcomings of traditional macromolecular stabilizers, which lack intrinsic antitumor activity and thus cannot enhance the efficacy of combined therapies.

[0023] The mitoxantrone-cuprous selenide nanocomposite particles obtained by this invention have uniform particle size (SEM average particle size of about 50 nm, DLS hydrated particle size of about 88.7 nm, PDI of 0.334), and the particle size does not change significantly in aqueous solution within 7 days, exhibiting excellent colloidal stability.

[0024] The mitoxantrone-copper selenide nanocomposite particles of the present invention have tumor microenvironment-responsive drug release characteristics: under simulated tumor microenvironment conditions (pH 5.5 and containing 10mM glutathione), the cumulative release rate of mitoxantrone reaches 69.7% within 2 hours and 77.0% within 24 hours, which can achieve glutathione-triggered efficient release of mitoxantrone, enhance chemotherapy selectivity and reduce systemic toxicity.

[0025] The inulin-based nanocomposite hydrogel of the present invention is formed in situ from natural polysaccharide inulin through a thermosensitive sol-gel transition. The preparation process is simple, the conditions are mild, and no cross-linking agent is required. It has good biocompatibility and injectability. The nanocomposite particles are uniformly dispersed in the gel matrix and can still form a stable hydrogel within 1 hour at a loading of 500 μg / mL.

[0026] The inulin-based nanocomposite hydrogel of the present invention exhibits excellent photothermal conversion performance under 808nm near-infrared laser irradiation. After 5 minutes of 1W / cm² laser irradiation, the temperature can reach 55~60℃. The resulting local high temperature directly induces photothermal ablation of tumor cells on the one hand, and promotes partial dissociation of the inulin hydrogel network on the other hand. This facilitates the continuous penetration of the released mitoxantrone-copper selenide nanocomposite particles into the tumor, overcoming the limitations of poor drug diffusion and retention in the gel matrix in traditional hydrogels, which makes it difficult to penetrate deep into the tumor.

[0027] The inulin-based nanocomposite hydrogel of this invention can form a local drug reservoir in situ after intratumoral or peritumoral injection, significantly prolonging the retention time at the tumor site compared with free nanoparticle suspensions. In vitro cell experiments showed that under 808nm laser irradiation, NP@Gel significantly enhanced the inhibition of CT26 and H22 cell viability (CT26 cell survival rate decreased to 16.9%, and H22 cell survival rate decreased to 22.2%), and induced a large number of apoptosis. In vivo animal experiments showed that under 808nm laser irradiation, NP@Gel achieved a tumor growth inhibition rate of up to 95.4% in H22 tumor-bearing mice, and the weight of mice in each treatment group remained stable, with good biocompatibility, achieving a potent chemotherapy-photothermal synergistic anti-tumor effect.

[0028] This invention combines a "small molecule drug stabilized nanoparticle" strategy with a "natural polysaccharide thermosensitive hydrogel" delivery system, providing a localized, stimulus-responsive, and synergistic integrated platform for tumor therapy. The preparation method is simple, low-cost, and easy to scale up, and has good prospects for clinical application.

[0029] Compared with existing macromolecular stabilizer solutions, this invention has the following significant advantages: First, mitoxantrone is a clinically approved chemotherapy drug with complete safety, pharmacokinetic, and toxicological data. As a stabilizer, it will not introduce new toxicological risks, and its clinical translation is less challenging. Second, mitoxantrone has a small molecular weight and a well-defined structure (molecular formula C). 22 H 28 N4O6), when used as a stabilizer in nanoparticle synthesis, does not have the problem of wide molecular weight distribution, exhibits excellent batch-to-batch reproducibility, and is beneficial for industrial quality control; thirdly, mitoxantrone has the dual functions of stabilizer and chemotherapeutic drug. Each molecule of mitoxantrone in the nanoparticle simultaneously undertakes the functions of structural stability and therapeutic delivery, realizing the atomic-level efficient utilization of "structural unit is functional unit" and avoiding the waste of the function of macromolecular stabilizers that "only stabilize and do not treat"; fourthly, mitoxantrone binds to the surface of cuprous selenide nanoparticles in a coordination form, with a strong binding. Compared with the post-loading strategy, it can significantly reduce the premature leakage of drugs in vivo, and can competitively dissociate and release under high glutathione concentrations in the tumor microenvironment, achieving site-specific drug delivery.

[0030] The preparation method of the inulin-based nanocomposite hydrogel described in this invention is carried out entirely in the aqueous phase, without the need for organic solvents, crosslinking agents, initiators, or high-temperature and high-pressure conditions. The preparation process is green and mild, and meets the requirements of Good Manufacturing Practice (GMP) for pharmaceuticals. Inulin is a natural fructan prebiotic that is widely available, inexpensive, and biodegradable. Its degradation products can be metabolized and utilized by the body. Inulin itself has probiotic functions such as regulating intestinal flora and producing short-chain fatty acids, which further enhances the safety and added value of the system. Attached Figure Description

[0031] Figure 1 The figure shows the preparation process and characterization results of the mitoxantrone-cuprous selenide nanocomposite particles in Example 1 of this invention; wherein: Figure 1 (a) is a schematic diagram of the preparation process of mitoxantrone-cuprous selenide nanocomposite particles; Figure 1 (b) Photographs of selenium nanoparticles (top) without mitoxantrone and cuprous selenide nanoparticles (bottom), showing rapid aggregation and precipitation. Figure 1 (c) A photograph of selenium nanoparticles loaded with mitoxantrone obtained after the addition of mitoxantrone, showing that the system remains stably dispersed; Figure 1 (d) is a photograph of the mitoxantrone-cuprous selenide nanocomposite particles obtained after the addition of copper chloride, showing that the system remains stably dispersed; Figure 1 (e) Figure 1 (f) Figure 1 (g) are particle size distribution diagrams of mitoxantrone-cuprous selenide nanocomposite particles obtained under conditions where the molar ratio of mitoxantrone to selenium is 1:6, 1:4, and 1:2, respectively. Figure 1 (h) is a scanning electron microscope image of mitoxantrone-cuprous selenide nanocomposite particles; Figure 1 (i) is a graph showing the change in particle size stability of mitoxantrone-cuprous selenide nanocomposite particles over 7 days; Figure 1 (j) shows the X-ray diffraction patterns of free mitoxantrone, mitoxantrone-free cuprous selenide precipitate, and mitoxantrone-cuprous selenide nanocomposite particles.

[0032] Figure 2 The figure shows the preparation and characterization results of inulin hydrogel and inulin-based nanocomposite hydrogel in Example 2 of this invention; wherein: Figure 2 (a) is a schematic diagram of the preparation process of blank inulin hydrogel (Gel) and inulin-based nanocomposite hydrogel (NP@Gel); Figure 2 (b) Photographs of the sol-gel transition process of Gel and NP@Gel; Figure 2 (c) Scanning electron microscope images of Gel and NP@Gel; Figure 2 (d) shows the rheological time scan curves of inulin hydrogels at different inulin concentrations (400, 500, 600 mg / mL).

[0033] Figure 3 The figure shows the photothermal performance test results of the mitoxantrone-cuprous selenide nanocomposite particles and inulin-based nanocomposite hydrogel in Example 3 of this invention; wherein: Figure 3 (a) Infrared thermographs of mitoxantrone-copper selenide nanocomposite particle suspensions at different concentrations (100, 200, 400, 500 μg / mL) after irradiation with an 808 nm (1 W / cm²) laser for 5 min. Figure 3(b) is an infrared thermogram of NP@Gel (with a nanocomposite particle concentration of 500 μg / mL) after irradiation with an 808 nm (1 W / cm²) laser for 5 min; Figure 3 (c) shows the temperature change curves of mitoxantrone-cuprous selenide nanocomposite particle suspensions of different concentrations during laser irradiation; Figure 3 (d) shows the temperature change curve of NP@Gel during laser irradiation; Figure 3 (e) is a photograph showing the changes in the state of NP@Gel before and after laser irradiation; Figure 3 (f) shows the temperature scan rheological curve of NP@Gel.

[0034] Figure 4 The figure shows the in vitro cytotoxicity and apoptosis experimental results of the inulin-based nanocomposite hydrogel in Example 4 of this invention; wherein: Figure 4 (a) The effect of Gel, NP and NP@Gel at different concentrations on the viability of CT26 colon cancer cells. "+" indicates irradiation with 808nm laser for 5 min at a power density of 1W / cm². Figure 4 (b) The effect of Gel, NP and NP@Gel on the viability of H22 liver cancer cells at different concentrations. "+" indicates irradiation with 808nm laser for 5 min at a power density of 1W / cm². Figure 4 (c) Flow cytometry apoptosis detection results of CT26 cells after treatment with Gel, NP, NP@Gel, NP(+) and NP@Gel(+); Figure 4 (d) shows the flow cytometry apoptosis detection results of H22 cells after treatment with Gel, NP, NP@Gel, NP(+) and NP@Gel(+).

[0035] Figure 5 The image shows the cell viability staining results of the inulin-based nanocomposite hydrogel in Example 4 of this invention; wherein: Figure 5 (a) is a live / dead double staining fluorescence microscopy image of CT26 cells after treatment with Gel, NP, NP@Gel, NP(+) and NP@Gel(+); Figure 5 (b) is a live / dead double staining fluorescence microscopy image of H22 cells after treatment with Gel, NP, NP@Gel, NP(+) and NP@Gel(+).

[0036] Figure 6 This is a diagram showing the in vivo photothermal imaging results of the inulin-based nanocomposite hydrogel in Example 5 of the present invention; wherein: Figure 6 (a) Infrared thermographs of H22 tumor-bearing mice after injection of free NP and irradiation with an 808nm laser for 5 minutes (n=3); Figure 6(b) Temperature change curves of mouse tumor sites injected with free NP during laser irradiation; Figure 6 (c) Infrared thermographs of H22 tumor-bearing mice after injection of NP@Gel and irradiation with an 808nm laser for 5 minutes (n=3); Figure 6 (d) shows the temperature change curve of the tumor site in mice injected with NP@Gel during laser irradiation.

[0037] Figure 7 This is a diagram showing the in vivo antitumor experimental results of the inulin-based nanocomposite hydrogel in Example 5 of the present invention; wherein: Figure 7 (a) is a schematic diagram of the anti-tumor experimental process; Figure 7 (b) shows the curves of tumor volume changes in mice in each group during the experiment; Figure 7 (c) shows the curves of weight changes in mice in each group during the experiment; Figure 7 (d) Photographs of tumor tissue samples from mice in each group at the end of the experiment (red crosses indicate mouse death); Figure 7 (e) is a statistical graph of tumor weight in each group of mice at the end of the experiment. Detailed Implementation

[0038] The technical solutions in the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of this application without creative effort are within the scope of protection of this application.

[0039] Unless otherwise stated, the reagents and materials used in the embodiments of this invention are all commercially available products in the art, such as mitoxantrone, sodium selenite, ascorbic acid, copper chloride, inulin, etc., all purchased from commercial suppliers; the cell lines CT26 (mouse colon cancer cells) and H22 (mouse liver cancer cells) can be obtained through public resource platforms such as ATCC or the Chinese Academy of Sciences Type Culture Collection Committee; the experimental animals are SPF-grade Balb / c mice. Where specific conditions are not specified in the embodiments, they should be performed according to conventional conditions in the art or conditions recommended by the manufacturer.

[0040] The main testing methods involved in the embodiments of this invention are as follows: the particle size and polydispersity index of nanoparticles were determined using dynamic light scattering (DLS); the morphology of nanoparticles was observed using scanning electron microscopy (SEM); the crystal structure of nanoparticles was determined using X-ray diffraction (XRD); the rheological properties of hydrogels were determined using rotational rheometer; the photothermal properties were determined using an 808nm near-infrared laser combined with an infrared thermal imager; cell viability was determined using the MTT assay; cell apoptosis was determined using Annexin V-FITC / PI double staining flow cytometry; cell live / dead status was observed using Calcein-AM / PI double staining combined with fluorescence microscopy; animal experiments were conducted according to the protocol approved by the laboratory animal ethics committee. Unless otherwise specified, the parameters such as concentration, ratio, temperature, and time in the embodiments of this invention can be reasonably adjusted within the disclosed numerical range. Those skilled in the art can select appropriate specific parameters according to actual needs, and these should not be construed as limiting the scope of protection of this invention.

[0041] Example 1: Preparation of mitoxantrone-cuprous selenide nanocomposite particles (NP)

[0042] This embodiment provides a method for preparing mitoxantrone-cuprous selenide nanocomposite particles (hereinafter referred to as NP), the core of which is to use mitoxantrone as a stabilizer to stabilize the cuprous selenide nanoparticles in situ.

[0043] The specific steps are as follows: First, prepare an aqueous solution of sodium selenite (concentration 10-50 mM, preferably 20 mM in this embodiment) and an aqueous solution of ascorbic acid (concentration 50-200 mM, preferably 100 mM in this embodiment). Under stirring, slowly add the aqueous solution of ascorbic acid to the sodium selenite solution, with a molar ratio of sodium selenite to ascorbic acid of 1:1 to 1:5, preferably 1:2 in this embodiment. React at room temperature (20-30℃) for 5-30 minutes. The ascorbic acid reduces the sodium selenite to obtain a selenium nanoparticle (SeNP) suspension, and the system appears orange-red to reddish-brown. It should be noted that the unstabilized original selenium nanoparticles are extremely unstable in aqueous solution and can rapidly aggregate and precipitate within minutes.

[0044] Subsequently, mitoxantrone (MIT) was dissolved in water to prepare a mitoxantrone solution with a concentration of 1-10 mg / mL, preferably 5 mg / mL in this embodiment. Under stirring, the mitoxantrone solution was rapidly added to the newly prepared selenium nanoparticle suspension to achieve a molar ratio of mitoxantrone to selenium of 1:6-1:2. In this embodiment, three molar ratios of 1:6, 1:4, and 1:2 were investigated, with 1:4 being the preferred ratio. Stirring was continued for 5-30 min to obtain selenium nanoparticles loaded with mitoxantrone. Experiments showed that the addition of mitoxantrone significantly stabilized the selenium nanoparticles, preventing their aggregation and precipitation. This indicates that the mitoxantrone molecule can interact with the surface of the selenium nanoparticles through coordination or adsorption via its anthraquinone ring and amino groups on its side chains, thereby exerting a stabilizer function.

[0045] Next, a copper chloride aqueous solution (concentration of 10-50 mM, preferably 20 mM in this embodiment) is prepared. Under stirring, the copper chloride aqueous solution is slowly added to the above-mentioned selenium nanoparticle suspension loaded with mitoxantrone, so that the molar ratio of copper to selenium is 1:1-2:1, preferably 1.5:1 in this embodiment. The reaction is continued at room temperature for 30-120 min, so that the selenium nanoparticles are converted into cuprous selenide (Cu2Se) nanoparticles, and the system gradually changes from orange-red to dark (dark green to black), forming stable cuprous selenide nanoparticles loaded with mitoxantrone.

[0046] Finally, the obtained reaction solution was transferred to a dialysis bag (molecular weight cutoff 8000~14000 Da) and dialyzed with deionized water for 24~48 h, changing the dialysis medium 3~5 times during the period to remove unreacted small molecules and byproducts. The product obtained after dialysis is an aqueous dispersion of mitoxantrone-cuprous selenide nanocomposite particles (NP), which was stored at 4℃ in the dark for later use.

[0047] Comparative Example: Cuprous selenide nanoparticles were prepared following the same steps as in Example 1, except that mitoxantrone was not added. The results showed that directly adding copper chloride solution to the freshly prepared selenium nanoparticle suspension resulted in the instantaneous formation of a large amount of dark green precipitate, making it impossible to obtain a stable nanoparticle dispersion. However, adding mitoxantrone followed by copper chloride resulted in long-term stable dispersion of nanoparticles. This comparative example demonstrates that mitoxantrone plays an indispensable stabilizing role in this invention, and its presence is crucial for the stable preparation of cuprous selenide nanoparticles.

[0048] The product obtained in Example 1 was characterized, and the results are as follows (see below). Figure 1 .

[0049] Figure 1(a) is a schematic diagram of the preparation process of mitoxantrone-cuprous selenide nanocomposite particles. It clearly shows the four-step process of "ascorbic acid reducing sodium selenite to generate selenium nanoparticles - adding mitoxantrone solution to form mitoxantrone-loaded selenium nanoparticles - adding copper chloride solution to convert selenium nanoparticles into cuprous selenide - dialysis purification to obtain NP". It reflects the technical route of in-situ synthesis of nanocomposite particles using mitoxantrone as a stabilizer.

[0050] Figure 1 (b) is a control experiment without the addition of mitoxantrone. The upper image shows that the original selenium nanoparticles rapidly aggregate and precipitate within minutes in the aqueous solution, while the lower image shows that a large amount of dark green precipitate is generated instantaneously after the direct addition of copper chloride. Neither of them can form a stable nanoparticle dispersion, which intuitively reveals the inherent instability of selenium / cuprous selenide nanoparticles under the condition of no stabilizer.

[0051] Figure 1 (c) is a photograph of selenium nanoparticles loaded with mitoxantrone obtained after the addition of mitoxantrone. It can be seen that the system presents a uniform dark dispersion with no obvious precipitation, indicating that mitoxantrone can effectively stabilize selenium nanoparticles.

[0052] Figure 1 (d) is a photograph of the mitoxantrone-cuprous selenide nanocomposite particles obtained after the addition of copper chloride. The system still maintains a uniformly dispersed dark suspension state without aggregation or precipitation, indicating that the obtained NP has good colloidal stability.

[0053] Figure 1 (e) Figure 1 (f) Figure 1 (g) are the DLS particle size distributions of NPs obtained under different mitoxantrone:se molar ratios (1:6, 1:4, 1:2). The results show that when the mitoxantrone:se molar ratio is 1:6 ( Figure 1 (e) NP exhibits a multimodal distribution, with a Z-average particle size of 269.1 nm and a polydispersity index (PDI) of 0.677. The particle size distribution is relatively wide, and some aggregation exists. When the MIT:Se molar ratio is 1:4 ( Figure 1 (f) The NP particle size distribution is unimodal and narrow, with a Z-average particle size of 88.7 nm and a PDI of 0.334; when the MIT:Se molar ratio is 1:2 ( Figure 1 (g) The particle size is further reduced to below 100 nm, and the distribution is narrower. Considering both drug loading and particle size uniformity, MIT:Se=1:4 is selected as the preferred ratio.

[0054] Figure 1(h) is a scanning electron microscope image of the NPs obtained with the preferred ratio (MIT:Se=1:4). The SEM image shows that the NPs have a regular spherical morphology, are uniformly dispersed and have no obvious agglomeration, with an average particle size of about 50 nm, which is basically consistent with the hydrated particle size (88.7 nm) measured by DLS (the particle size measured by DLS includes the hydration layer, so it is slightly larger than the SEM particle size).

[0055] Figure 1 (i) is a graph showing the particle size stability changes of NP in aqueous solution over 7 days. The results show that after 7 days of storage at 4°C, the hydrated particle size and PDI of NP did not change significantly, indicating that NP has good storage stability and can meet the needs of subsequent formulation preparation and clinical application.

[0056] Figure 1 (j) shows the XRD patterns of free mitoxantrone, mitoxantrone-free cuprous selenide precipitate (Cu2Se precipitate), and NP. The results show that the free mitoxantrone powder exhibits sharp characteristic diffraction peaks, indicating that it exists in a crystalline state; the Cu2Se precipitate shows weak diffraction peaks at approximately 27° and 45° 2θ, corresponding to the crystalline characteristics of cuprous selenide; the characteristic peaks of cuprous selenide are still present in the diffraction pattern of NP, while the sharp crystalline diffraction peaks of free mitoxantrone have completely disappeared, indicating that mitoxantrone does not exist in a free crystalline state in NP, but is bound to the surface of cuprous selenide nanoparticles in the form of coordination or adsorption, which corroborates the structural characteristics of mitoxantrone as a stabilizer participating in the assembly of nanoparticles.

[0057] In addition, the drug loading capacity (DLC) and drug loading efficiency (DLE) of NP under different MIT:Se molar ratios were determined: as the amount of mitoxantrone added increased, the DLC of NP increased from 9.98% (MIT:Se=1:6) to 22.43% (MIT:Se=1:2), while the DLE decreased accordingly; a good balance between drug loading capacity and drug loading efficiency was achieved at MIT:Se=1:4, so it was the preferred option.

[0058] Example 2: Preparation of inulin hydrogel (Gel) and inulin-based nanocomposite hydrogel (NP@Gel)

[0059] This embodiment provides a method for preparing blank inulin hydrogel (Gel) and inulin-based nanocomposite hydrogel (NP@Gel).

[0060] Preparation of inulin hydrogel (Gel): Inulin powder was weighed and added to deionized water. The mixture was stirred and dissolved in a water bath at 30-40℃ (preferably 37℃ in this embodiment) to prepare an inulin precursor solution with an inulin concentration of 400-600 mg / mL. In this embodiment, three concentrations of 400 mg / mL, 500 mg / mL, and 600 mg / mL were investigated. The inulin precursor solution was placed in a low-temperature environment (0-10℃, preferably 4℃ in this embodiment) and allowed to stand. The inulin underwent a temperature-sensitive sol-gel transition, forming a white, opaque inulin hydrogel (Gel) within 0.52 h.

[0061] Preparation of inulin-based nanocomposite hydrogel (NP@Gel): The aqueous dispersion of mitoxantrone-cuprous selenide nanocomposite particles (NP) obtained in Example 1 was concentrated or diluted to a suitable concentration. The NP dispersion was then mixed with the above-mentioned inulin precursor solution in a certain proportion, so that the final concentration of NP in the system was 50~500 μg / mL (preferably 500 μg / mL in this example). The mixture was stirred and mixed evenly at 30-40℃ to ensure that the NP was uniformly dispersed in the inulin precursor solution. Subsequently, the mixture was placed in an environment of 0~10℃ (preferably 4℃ in this example) for standing. The system underwent a thermosensitive sol-gel transition, and an in-situ uniformly dispersed inulin-based nanocomposite hydrogel (NP@Gel) was formed within 1 hour. Macroscopic observation confirmed that even at a high NP loading of 500 μg / mL, the composite system could still maintain the ability to form a stable hydrogel within 1 hour, without phase separation or gel collapse.

[0062] The product obtained in Example 2 was characterized, and the results are as follows (see below). Figure 2 .

[0063] Figure 2 (a) is a schematic diagram of the preparation process of Gel and NP@Gel. It clearly shows that: in the blank group, the inulin precursor solution was dissolved at 37°C and then cooled to 4°C to form gel; in the composite group, NP dispersion was added to the inulin precursor solution, mixed well, and then cooled to 4°C to form NP@Gel. The entire preparation process requires no crosslinking agent, initiator, or organic solvent, and the process is simple and mild, meeting the requirements of green preparation and clinical application.

[0064] Figure 2 (b) Photographs of the sol-gel transition process of Gel and NP@Gel. It can be seen that the inulin solution is a flowable, clear liquid (sol state) at 37℃, and gradually transforms into a non-flowing white gel (gel state) after being transferred to 4℃ and allowed to stand. NP@Gel, due to its NP content, exhibits a uniform dark appearance and does not flow when inverted, demonstrating the integrity of the gel structure. These results indicate that the inulin system possesses typical temperature-sensitive sol-gel transition characteristics, and that the loading of NP does not affect the gelation process.

[0065] Figure 2(c) are scanning electron microscope images of Gel and NP@Gel. The SEM images show that Gel exhibits a typical porous three-dimensional network structure with uniform pore size; NP@Gel also exhibits a porous network structure, with NP particles uniformly distributed in the gel skeleton and pores in the form of spherical particles without obvious aggregation, proving that NP is uniformly dispersed in the inulin hydrogel matrix and that the two have good compatibility.

[0066] Figure 2 (d) Rheological time-scan curves of inulin hydrogels at different inulin concentrations (400, 500, and 600 mg / mL). The results showed that the viscosity of the 400 mg / mL inulin solution began to increase within 30 min, formed a primary gel at 1 h, and matured after 2 h, with a storage modulus G′ of approximately 20 Pa at 1 h. The 500 mg / mL inulin solution completed gelation within 1 h, with G′ of approximately 1900 Pa at 1 h. The gelation behavior of the 600 mg / mL inulin solution was similar to that of the 500 mg / mL solution, with G′ of approximately 11000 Pa at 1 h, reaching over 25000 Pa after 2 h. Considering gelation rate, gel strength, injectability, and material usage, 500 mg / mL was selected as the optimal inulin concentration.

[0067] Example 3: Photothermal Properties Testing of Mitoxanthraquinone-Cuprous Selenide Nanocomposite Particles and Inulin-Based Nanocomposite Hydrogels

[0068] This embodiment examines the photothermal conversion performance of NP and NP@Gel under 808nm near-infrared laser irradiation.

[0069] Photothermal performance testing method: NP aqueous dispersions with concentrations of 100, 200, 400, and 500 μg / mL were prepared, as well as NP@Gel samples with a final NP concentration of 500 μg / mL. The samples were irradiated with an 808 nm near-infrared laser at a power density of 1 W / cm² for 5 min. At the same time, the temperature change of the samples was recorded using an infrared thermal imager, and infrared thermal images were taken.

[0070] The results are as follows, see below. Figure 3 .

[0071] Figure 3 (a) Infrared thermograms of NP suspensions at different concentrations after irradiation with an 808 nm (1 W / cm²) laser for 5 min. The results show that as the NP concentration increases, the sample temperature increases significantly, and the color of the thermogram gradually changes from blue (low temperature) to red (high temperature), which intuitively presents the concentration-dependent photothermal heating effect.

[0072] Figure 3(b) is an infrared thermogram of NP@Gel (NP concentration of 500 μg / mL) after irradiation with an 808 nm (1 W / cm²) laser for 5 min. The results show that NP@Gel also exhibits a significant heating effect, and the thermogram shows a uniform high-temperature red distribution, indicating that NP is uniformly dispersed in the gel matrix and maintains good photothermal conversion performance, and the gel matrix does not hinder photothermal conversion.

[0073] Figure 3 (c) shows the temperature change curves of NP suspensions at different concentrations during laser irradiation. The results show that the temperature of the pure water control group remained basically unchanged; when the NP concentration was 100 μg / mL, the temperature rose to about 42℃ after 5 min of irradiation; at 200 μg / mL, it rose to about 48.3℃; at 400 μg / mL, it rose to about 54.3℃; and at 500 μg / mL, it rose to about 59.7℃. The temperature increased with increasing concentration, showing a good concentration dependence, and the temperature rise was rapid with a stable plateau.

[0074] Figure 3 (d) shows the temperature change curve of NP@Gel during laser irradiation. The results show that the temperature of NP@Gel (NP concentration of 500 μg / mL) reached about 58.5℃ after irradiation with an 808nm laser at 1W / cm² for 5 minutes, which is comparable to that of free NP suspension at the same concentration (59.7℃). This further proves that the gel matrix has an excellent effect on preserving the photothermal properties of NP, which is sufficient to meet the high temperature conditions required for photothermal therapy (it is generally believed that temperatures above 45℃ can effectively kill tumor cells).

[0075] Figure 3 (e) shows the state changes of NP@Gel before and after laser irradiation. The results show that after irradiation with an 808nm laser, NP@Gel exhibits obvious partial dissociation, with the gel structure changing from an intact state to a locally loose and partially liquefied state, proving that the photothermal effect can trigger the partial dissociation of the inulin hydrogel network. This phenomenon is one of the key functions of this invention: local heating promotes the partial dissociation of the inulin hydrogel network, which is beneficial for the continuous penetration of the released mitoxantrone-cuprous selenide nanocomposite particles into the tumor, enhancing the synergistic chemo-photothermal cytotoxicity against cancer cells.

[0076] Figure 3 (f) shows the temperature-scanned rheological curves of NP@Gel. The results show that as the temperature increases from room temperature to 60℃, the storage modulus G′ of NP@Gel gradually decreases, dropping to approximately 200 Pa at 60℃. This indicates that the gel network softens and partially dissociates at high temperatures. Figure 3 (e) The observed phenomena are consistent, confirming the photothermal responsive dissociation characteristics of NP@Gel from a rheological perspective.

[0077] Furthermore, this embodiment also investigated the photothermal stability of NP. Multiple cycles of "808nm laser irradiation-natural cooling" were performed on 500 μg / mL NP suspension and NP@Gel (each cycle consisting of 1 W / cm² irradiation for 5 min followed by natural cooling to room temperature), and the temperature rise in each cycle was recorded. The results showed that after 5 irradiation-cooling cycles, the temperature rise curves of NP and NP@Gel essentially overlapped, with no significant decrease in the maximum temperature rise. This indicates that NP possesses excellent photothermal stability and reusability, maintaining stable photothermal conversion performance under multiple laser irradiations, which is particularly important for treatment regimens requiring multiple irradiations in clinical practice.

[0078] Example 4: Tumor microenvironment-responsive release experiment of mitoxantrone-cuprous selenide nanocomposite particles

[0079] This embodiment investigates the release behavior of mitoxantrone in NP under different conditions to verify its responsive release characteristics in the tumor microenvironment (low pH, high glutathione concentration).

[0080] Release experiment method: Take the NP aqueous dispersion obtained in Example 1 (the content of mitoxantrone is known) and transfer it to a dialysis bag (molecular weight cutoff 8000~14000 Da). Immerse it in the following release media respectively: (1) phosphate buffer at pH 7.4 (simulating normal physiological environment); (2) acetate buffer at pH 5.5 (simulating weakly acidic microenvironment of tumor tissue); (3) acetate buffer at pH 5.5 containing 10 mM glutathione (GSH) (simulating highly reducing microenvironment in tumor cells); (4) control medium at pH 7.4 containing 10 mM glutathione. The release system was placed in a constant temperature shaker at 37°C (oscillation rate 100 rpm), and samples were taken at predetermined time points (0.5h, 1h, 2h, 4h, 6h, 8h, 12h, 24h). The concentration of mitoxantrone in the release medium was determined by ultraviolet-visible spectrophotometry (the characteristic absorption wavelength of mitoxantrone is about 610 nm) or high performance liquid chromatography, and the cumulative release rate was calculated.

[0081] The results showed that mitoxantrone was released slowly in phosphate buffer at pH 7.4, with a cumulative release rate of less than 40% after 24 hours, indicating that NP is structurally stable in a neutral physiological environment, which can effectively prevent premature leakage of the drug in the bloodstream or normal tissues and reduce systemic toxicity. In acetate buffer at pH 5.5, the release rate of mitoxantrone was accelerated, reflecting the promoting effect of a weakly acidic environment on drug release. Under simulated tumor microenvironment conditions at pH 5.5 containing 10 mM glutathione, the release of mitoxantrone was significantly accelerated, with a cumulative release rate of 69.7% within 2 hours, which plateaued after 24 hours, with a cumulative release rate of approximately 77.0%. These results indicate that NP possesses redox-responsive characteristics. High concentrations of glutathione can competitively disrupt the coordination binding between mitoxantrone and cuprous selenide, achieving glutathione-triggered efficient release of mitoxantrone. Furthermore, the inherent low pH and high glutathione characteristics of the tumor microenvironment (the glutathione concentration in tumor cells can be several to tens of times higher than in normal cells) enable NP to specifically release chemotherapeutic drugs at the tumor site, enhancing the efficacy of chemotherapy while reducing damage to normal tissues, embodying the design concept of "intelligent response and on-demand release." Example 5: In vitro cytotoxicity, apoptosis, and live / dead cell staining experiments.

[0082] This embodiment investigates the cytotoxicity of Gel, NP, and NP@Gel against CT26 mouse colon cancer cells and H22 mouse liver cancer cells, as well as the synergistic killing effect of chemotherapy-photothermal therapy, through in vitro cell experiments.

[0083] Cell culture: CT26 cells and H22 cells were cultured in RPMI-1640 medium (H22 cells were in suspension culture) or DMEM medium (CT26 cells were in adherent culture) containing 10% fetal bovine serum and 1% penicillin-streptomycin, respectively, in an incubator at 37°C and 5% CO2 saturated humidity.

[0084] Experimental groups: The experiment was divided into three groups: a Gel group (blank inulin hydrogel), an NP group (free mitoxantrone-cuprous selenide nanocomposite particles), and an NP@Gel group (inulin-based nanocomposite hydrogel). Each group was further divided into two subgroups: one with light exposure (+) and one without light exposure. The light exposure conditions were 808 nm laser, power density 1 W / cm², and irradiation for 5 min. A blank control group was also included. The drug (NP) concentration gradients were set at 6.25, 12.50, 25.00, 50.00, and 100.00 μg / mL.

[0085] Cytotoxicity assay (MTT method): Cells were seeded in 96-well plates and cultured overnight. Culture medium containing different concentrations of samples was added and incubated for 24 h. The light-treated group was irradiated with 808 nm laser (1 W / cm², 5 min) 4 h after sample addition and incubated for another 24 h. Then, MTT solution (5 mg / mL) was added to each well and incubated for 4 h. The supernatant was discarded, and dimethyl sulfoxide was added to dissolve formazan crystals. The absorbance was measured at 490 nm, and cell viability was calculated.

[0086] The results are as follows, see below. Figure 4 .

[0087] Figure 4 (a) shows the cytotoxicity results of Gel, NP, and NP@Gel on CT26 cells at different concentrations. "+" indicates irradiation with 808nm laser for 5 min at a power density of 1W / cm². The results showed that the cell survival rate of the Gel group was greater than 85% at all concentrations, indicating that the blank inulin hydrogel had no obvious toxicity to CT26 cells and good biocompatibility. The NP group and NP@Gel group showed concentration-dependent cytotoxicity under light-free conditions, with cell survival rates of 53.6% and 51.5% at 100μg / mL, respectively. After irradiation with 808nm laser, the cytotoxicity of the NP(+) group and NP@Gel(+) group was significantly enhanced, with cell survival rates decreasing to 18.4% and 16.9% at 100μg / mL, respectively, reflecting the synergistic killing effect of chemotherapy and photothermal therapy. The NP@Gel(+) group showed a slightly better killing effect than the NP(+) group at all concentrations, which may be attributed to the sustained-release characteristics and continuous effect of the nanocomposite particles in the hydrogel system.

[0088] Figure 4 (b) The cytotoxicity results of Gel, NP, and NP@Gel on H22 cells at different concentrations. The results showed that the Gel group had no activity against H22 cells (cell survival rate was close to 100%); the NP and NP@Gel groups had cell survival rates greater than 60% at concentrations below 50 μg / mL, with the NP group showing a cell survival rate of 21.8% and the NP@Gel group 22.2% at 100 μg / mL; after laser irradiation, cell survival rates further decreased at all concentrations, with the NP(+) group and NP@Gel(+) group showing the strongest killing effect at 100 μg / mL. These results indicate that the synergistic effect of chemotherapy and photothermal therapy is also significant on H22 cells, and NP@Gel has a synergistic therapeutic effect comparable to free NP, while also possessing the advantage of local retention.

[0089] Apoptosis detection (flow cytometry): Cells were seeded in 6-well plates and cultured overnight. Gel, NP, and NP@Gel samples (NP concentration of 100 μg / mL) were added and incubated for 4 h. The light group was irradiated with 808 nm laser (1 W / cm²) for 5 min and incubated for 24 h. Cells were collected, stained with Annexin V-FITC / PI double staining kit, and the apoptosis rate was detected by flow cytometry.

[0090] Figure 4 (c) Flow cytometry apoptosis detection results of CT26 cells after treatment with Gel, NP, NP@Gel, NP(+), and NP@Gel(+). The results showed that the survival rate of CT26 cells in the control group (untreated) was 94.1%, and that in the Gel group was 94.1%, indicating that the blank gel had no significant pro-apoptotic effect; the NP group and NP@Gel group induced only a small number of apoptosis under light-free conditions; while the NP(+) group and NP@Gel(+) group induced a large number of apoptosis and necrosis after laser irradiation, among which the proportion of late apoptosis and necrosis in the NP@Gel(+) group was significantly increased, and the synergistic therapeutic effect was significant.

[0091] Figure 4 (d) Flow cytometry results of apoptosis detection in H22 cells after treatment with Gel, NP, NP@Gel, NP(+), and NP@Gel(+). Results showed that the survival rate of H22 cells in the control group was 95.3%, and in the Gel group it was 94.6%. The apoptosis rate in the NP(+) and NP@Gel(+) groups increased significantly after laser irradiation, consistent with the trend observed in CT26 cells, further confirming the mechanism of chemotherapy-photothermal synergistic apoptosis induction.

[0092] Live / dead cell double staining assay: Cells were seeded in culture dishes and treated according to the above grouping (NP concentration 100 μg / mL, light conditions as above). Calcein-AM and PI staining solutions were added and incubated for 15–30 min. After washing with PBS, the cells were observed and photographed under a fluorescence microscope. Live cells were stained green by Calcein-AM, and dead cells were stained red by PI.

[0093] Figure 5 (a) Viable / dead double-stain fluorescence microscopy images of CT26 cells after treatment with Gel, NP, NP@Gel, NP(+), and NP@Gel(+). The results showed that the cells in the control group and Gel group exhibited dense green fluorescence, indicating good cell viability; the NP group and NP@Gel group showed partial red fluorescence under no-light conditions; the green fluorescence in the NP(+) group and NP@Gel(+) group decreased significantly and the red fluorescence increased significantly after laser irradiation, indicating that most cells died, which directly confirmed the synergistic killing effect of chemotherapy-photothermal therapy.

[0094] Figure 5 (b) are fluorescence micrographs of H22 cells after treatment with Gel, NP, NP@Gel, NP(+), and NP@Gel(+). H22 cells are suspension cells. The staining results showed that the control group and Gel group were mainly green fluorescence; the NP(+) group and NP@Gel(+) group showed significantly increased red fluorescence and significantly reduced cell viability, consistent with the results of MTT and flow cytometry apoptosis.

[0095] To further elucidate the mechanism of action of the synergistic therapy, this embodiment also observed the cell morphology before and after laser irradiation. After irradiation with 808nm laser, the cells in the NP(+) group and the NP@Gel(+) group showed obvious morphological changes: adherent CT26 cells showed shrinkage, rounding and detachment, and suspended H22 cells showed apoptosis or necrosis characteristics such as cell membrane blistering and fragmentation, while the cells in the unirradiated group had basically normal morphology. Based on the flow cytometry apoptosis results, the synergistic antitumor mechanism of the system described in this invention can be inferred to include: First, under 808nm laser irradiation, the copper selenide nanoparticles undergo efficient photothermal conversion through localized surface plasmon resonance, generating localized high temperatures that directly lead to protein denaturation, cell membrane rupture, and thermal ablation in tumor cells; Second, the photothermal effect and the reducing properties of glutathione in the tumor microenvironment jointly promote the release of mitoxantrone from the nanocomposite particles, allowing chemotherapeutic drugs to exert cytotoxicity through mechanisms such as embedding between DNA base pairs in tumor cells and inhibiting topoisomerase II; Third, the combined effect of chemotherapy and photothermal action can induce tumor cells to produce excessive reactive oxygen species, triggering oxidative stress damage and further amplifying the cell-killing effect; Fourth, the inulin hydrogel matrix anchors the nanocomposite particles to the tumor site, prolonging the interaction time between the drug and the photothermal agent, and achieving continuous delivery of the nanocomposite particles to the deeper parts of the tumor through photothermal-triggered gel dissociation. The synergistic superposition of these multiple mechanisms resulted in the NP@Gel(+) group exhibiting significantly better antitumor effects than single treatment modalities both in vivo and in vitro.

[0096] Example 6: In vivo anti-tumor experiment

[0097] This embodiment investigates the in vivo photothermal properties and the synergistic antitumor effect of chemotherapy-photothermal combination using an H22 tumor-bearing mouse model.

[0098] Experimental methods: 6-8 week old SPF-grade Balb / c mice were selected, and H22 cells (approximately 1×10⁻⁶) were subcutaneously inoculated under the armpits of the mice. 6H22 tumor-bearing mouse model was established. When the tumor volume grew to approximately 100 mm³, the tumor-bearing mice were randomly divided into 5 groups: control group (saline), NP group (intratumoral injection of free NP, no light exposure), NP@Gel group (intratumoral injection of NP@Gel, no light exposure), NP(+) group (intratumoral injection of free NP followed by 808 nm laser irradiation), and NP@Gel(+) group (intratumoral injection of NP@Gel followed by 808 nm laser irradiation); 8 mice in each group (thermal imaging group n=3). The drug dosage was 5 mg / kg (preferred range 1~10 mg / kg) based on NP, and the injection volume was approximately 50~100 μL. In the light exposure group, the tumor site was irradiated with an 808 nm laser (1 W / cm²) for 5 min 1 h after injection. During the treatment period, the tumor volume and mouse weight were measured every other day, and the survival status of the mice was recorded; at the end of the experiment (day 11 or day 14), the mice were sacrificed, the tumor tissue was dissected and weighed, and the tumor growth inhibition rate was calculated. Tumor volume was calculated using the formula V = length × width² / 2; tumor inhibition rate was calculated as (1 - average tumor weight in the treatment group / average tumor weight in the control group) × 100%.

[0099] The results of in vivo photothermal imaging are as follows, see below. Figure 6 .

[0100] Figure 6 (a) Infrared thermographic images of H22 tumor-bearing mice after intratumoral injection of free NP and irradiation with an 808 nm laser (1 W / cm²) for 5 min (n=3). The results show that the temperature of the tumor site in mice injected with free NP rises rapidly under laser irradiation. The temperature of the tumor site can reach about 40 °C at 1 min and exceeds 45 °C at 5 min. The thermographic images show that the tumor area presents obvious bright high-temperature areas, but the heat distribution is relatively concentrated on the surface.

[0101] Figure 6 (b) shows the temperature change curve of the tumor site in mice injected with free NP during laser irradiation. The results showed that the temperature of the tumor site in the NP group mice rose rapidly over time and tended to stabilize within a few minutes. At 5 minutes, the temperature exceeded 45°C, which could reach the effective temperature window for photothermal therapy. However, the temperature increase was slightly lower than that in the NP@Gel group.

[0102] Figure 6 (c) Infrared thermography of H22 tumor-bearing mice after intratumoral injection of NP@Gel and irradiation with an 808nm laser (1W / cm²) for 5 min (n=3). The results showed that the tumor site of the mice injected with NP@Gel experienced a more rapid and significant temperature increase under laser irradiation, exceeding 46℃ at 1 min and 55℃ at 5 min. Moreover, the high-temperature area was more uniformly distributed and more stable, demonstrating the enhanced effect of the hydrogel local drug reservoir on the retention and enrichment of photothermal agents.

[0103] Figure 6 (d) shows the temperature change curve of the tumor site in mice injected with NP@Gel during laser irradiation. The results showed that the tumor site temperature in the NP@Gel group exceeded 55℃ at 5 min, which was significantly higher than that in the free NP group (>45℃). This further proves that NP@Gel achieves more efficient photothermal heating by prolonging the residence time of nanoparticles in the tumor site and increasing the local photothermal agent concentration, thus providing a sufficient thermal basis for synergistic therapy.

[0104] The anti-tumor effects are as follows, see below. Figure 7 .

[0105] Figure 7 (a) is a schematic diagram of the anti-tumor experiment process, showing the complete experimental process of "tumor inoculation - group drug administration (intratumoral injection of NP or NP@Gel) - 808nm laser irradiation (1W / cm², 5min) - periodic measurement of tumor volume and weight - tumor dissection at the experimental endpoint". Day 0 is the time point for drug administration and irradiation, and Day 1, 3, 5, etc. are the subsequent measurement time points.

[0106] Figure 7 (b) shows the tumor volume change curves of each group of mice during the experiment. The results showed that the tumors in the control group grew rapidly, with an average tumor volume of 1620 mm³ by day 11; the tumor growth in the NP group (no light exposure) was somewhat inhibited, with an average of 1180 mm³ by day 11; the tumor growth in the NP@Gel group (no light exposure) was further inhibited, with an average of 920 mm³ by day 11, which was better than that in the free NP group, indicating that the hydrogel reservoir prolonged the retention time of nanoparticles and enhanced the effect of chemotherapy alone; the tumor volume in the NP(+) group (photothermal + chemotherapy) was significantly reduced; the tumor growth in the NP@Gel(+) group almost completely stopped, and the tumor volume basically stopped increasing from day 7, with an average of only 343 mm³ by day 11, showing the most outstanding therapeutic effect.

[0107] Figure 7 (c) shows the changes in mouse body weight in each group during the experiment. The results show that the body weight of mice in each group remained stable throughout the experiment, with no significant downward trend, indicating that none of the drug administration groups (including the NP@Gel(+) group) caused significant systemic toxicity, proving that the nanocomposite hydrogel system has good in vivo biocompatibility and safety.

[0108] Figure 7(d) Photographs of tumor tissue samples from mice in each group at the end of the experiment (red crosses indicate mouse deaths). The results showed that 2 mice died in the control group and NP group, 1 mouse died in the NP(+) group, while all 8 mice in the NP@Gel(+) group survived. This indicates that the NP@Gel(+) treatment group not only had the best therapeutic effect, but also significantly improved the survival of tumor-bearing mice, demonstrating the positive impact of synergistic treatment on survival prognosis.

[0109] Figure 7 (e) is a statistical graph of tumor weight in each group of mice at the end of the experiment. The results showed that the average tumor weight in the control group was 3145±924 mg; in the NP group it was 1642±123 mg; in the NP@Gel group it was 1141±404 mg; the NP(+) group was significantly lower than the no-light group; the average tumor weight in the NP@Gel(+) group was only 144±152 mg. The tumor growth inhibition rate was calculated to be 47.8% in the NP group, 63.7% in the NP@Gel group, 84.2% in the NP(+) group, and as high as 95.4% in the NP@Gel(+) group, showing the strongest synergistic anti-tumor effect. At the same time, in vivo photothermal imaging ( Figure 6 ) and anti-tumor results ( Figure 7 The results corroborate each other, proving that the inulin-based nanocomposite hydrogel achieves efficient synergy between chemotherapy and photothermal therapy through multiple mechanisms: "local retention enhancement, photothermal conversion, gel dissociation and release, and chemotherapy penetration".

[0110] Example 7: Biocompatibility and Safety Assessment

[0111] This embodiment evaluates the biocompatibility of inulin-based nanocomposite hydrogels. Specifically, it includes: (1) In vitro cell compatibility: As shown in Example 5, the survival rate of the blank Gel group in CT26 and H22 cells was greater than 85% (CT26) or close to 100% (H22), proving that the inulin hydrogel matrix itself has no cytotoxicity; (2) In vivo safety: As shown in Example 6, the weight of mice in each group remained stable throughout the treatment period, with no obvious signs of emaciation, lethargy or other abnormalities. All 8 mice in the NP@Gel(+) group survived, and no obvious systemic toxicity was observed; (3) Safety of ex vivo tissues: Histological examination of the main organs (heart, liver, spleen, lungs, and kidneys) at the experimental endpoint revealed no obvious pathological damage, further proving that the system has good biocompatibility and high safety.

[0112] The above embodiments confirm that the inulin-based nanocomposite hydrogel of the present invention possesses the following characteristics: First, mitoxantrone, as a structurally well-defined small molecule chemotherapeutic drug and stabilizer, directly participates in the in-situ synthesis of cuprous selenide nanoparticles, endowing the nanoparticles with colloidal stability and intrinsic chemotherapeutic function, without the need for inert macromolecular stabilizers, overcoming the defects of existing technologies such as wide molecular weight distribution of stabilizers, poor batch reproducibility, and lack of intrinsic antitumor activity; Second, inulin, as a natural polysaccharide thermosensitive hydrogel matrix, can be gelled in situ through simple dissolution-cooling, with a mild process, no cross-linking agents, and injectability, significantly prolonging the residence time of nanoparticles at the tumor site; Third, under 808nm near-infrared laser irradiation, the local high temperature generated by the efficient photothermal conversion of cuprous selenide nanoparticles can directly kill tumor cells and trigger partial dissociation of the inulin hydrogel network, promoting the deep penetration of nanocomposite particles into the tumor and releasing mitoxantrone in response to the tumor microenvironment (low pH, high glutathione), achieving synergistic effect of chemotherapy-photothermal, with a tumor inhibition rate of 95.4%. It is important to emphasize that all the aforementioned effects are achieved based on the core concept of "in-situ synthesis of cuprous selenide nanocomposite particles using mitoxantrone as a stabilizer." This concept unifies the stability, drug loading, release behavior, and photothermal properties of the nanoparticles, and any simple physical mixing scheme deviating from this core concept cannot achieve the aforementioned synergistic effects. Therefore, this invention provides a simple and effective strategy for localized, stimulus-responsive, and synergistic tumor therapy, and has broad clinical application prospects.

[0113] The embodiments described herein are preferred embodiments of the present invention and are not intended to limit the scope of protection of the present invention. Therefore, all equivalent changes made in accordance with the structure, shape, and principle of the present invention should be covered within the scope of protection of the present invention.

Claims

1. An inulin-based nanocomposite hydrogel, characterized in that, The inulin-based nanocomposite hydrogel comprises an inulin hydrogel matrix and mitoxantrone-copper selenide nanocomposite particles dispersed in the inulin hydrogel matrix. The mitoxantrone-copper selenide nanocomposite particles are formed by in-situ stabilization of copper selenide nanoparticles with mitoxantrone as a stabilizer, and the mitoxantrone is coordinated to the surface of the copper selenide nanoparticles. The inulin hydrogel matrix is ​​formed by thermosensitive sol-gel transformation of inulin aqueous solution, and the mitoxantrone-copper selenide nanocomposite particles are uniformly dispersed in the inulin hydrogel matrix. The inulin-based nanocomposite hydrogel can generate photothermal conversion under near-infrared light irradiation and can release mitoxantrone in response to the tumor microenvironment.

2. The inulin-based nanocomposite hydrogel according to claim 1, characterized in that, In the mitoxantrone-copper selenide nanocomposite particles, the molar ratio of mitoxantrone to selenium is 1:6 to 1:2; the average particle size of the mitoxantrone-copper selenide nanocomposite particles is 50 to 100 nm; and the polydispersity index of the mitoxantrone-copper selenide nanocomposite particles is not higher than 0.

4.

3. The inulin-based nanocomposite hydrogel according to claim 1, characterized in that, The concentration of inulin in the inulin aqueous solution is 400~600 mg / mL; the gelation time of the inulin-based nanocomposite hydrogel is 0.5~2 h.

4. A method for preparing mitoxantrone-cuprous selenide nanocomposite particles, characterized in that, The process includes the following steps: reducing sodium selenite with ascorbic acid to obtain selenium nanoparticles; adding mitoxantrone solution to the suspension of the selenium nanoparticles to obtain selenium nanoparticles loaded with mitoxantrone; then adding copper chloride solution to convert the selenium nanoparticles into cuprous selenide nanoparticles, and purifying them by dialysis to obtain the mitoxantrone-cuprous selenide nanocomposite particles.

5. A method for preparing an inulin-based nanocomposite hydrogel, characterized in that, The process includes the following steps: dissolving inulin in water and stirring at 30-40°C to obtain an inulin precursor solution; dispersing mitoxantrone-cuprous selenide nanocomposite particles prepared by the method described in claim 4 in the inulin precursor solution, wherein the concentration of the mitoxantrone-cuprous selenide nanocomposite particles is 50-500 μg / mL; and then cooling and allowing the system to stand at 0-10°C to allow the system to undergo a thermosensitive sol-gel transition, thereby forming the inulin-based nanocomposite hydrogel in situ.

6. The inulin-based nanocomposite hydrogel according to claim 1, characterized in that, The inulin-based nanocomposite hydrogel can responsively release mitoxantrone under simulated tumor microenvironment conditions: under pH 5.0-6.0 and containing 5-20 mM glutathione, the cumulative release rate of mitoxantrone is 60%-75% within 2 hours and 70%-80% within 24 hours; and under near-infrared light irradiation, the inulin hydrogel matrix undergoes partial dissociation, promoting the release and penetration of the mitoxantrone-cuprous selenide nanocomposite particles.

7. The inulin-based nanocomposite hydrogel according to claim 1, characterized in that, The inulin-based nanocomposite hydrogel was irradiated with an 808nm near-infrared laser with a power density of 0.5~2W / cm² for 5 minutes, and the temperature rose to 45~65℃.

8. The use of an inulin-based nanocomposite hydrogel according to any one of claims 1 to 3, 6, and 7 in the preparation of a drug or formulation for tumor chemotherapy-photothermal synergistic therapy.

9. The application according to claim 8, characterized in that, The drug or preparation is administered via intratumoral or peritumoral injection, forming a gel reservoir in situ at the injection site. After administration, the tumor site is irradiated with a near-infrared laser, which, while achieving photothermal ablation, triggers partial dissociation of the inulin-based nanocomposite hydrogel, promoting the penetration of the mitoxantrone-cuprous selenide nanocomposite particles into the deeper layers of the tumor and releasing mitoxantrone, thus achieving synergistic effects of chemotherapy and photothermal therapy. The near-infrared laser is an 808nm laser with a power density of 0.5~2W / cm² and an irradiation time of 3~10min.

10. The application according to claim 8, characterized in that, The tumor is a solid tumor, including liver cancer, colorectal cancer, breast cancer, cervical cancer, melanoma, or lung cancer; the inulin-based nanocomposite hydrogel has an inhibition rate of no less than 90% on tumor growth.

Citation Information

Patent Citations

  • Mitoxantrone nano calcium hydrophosphate preparation and preparation method thereof

    CN102579355A

  • Preparation method of mitoxantrone supported nano-particle taking fluorinated graphene as carrier

    CN109125272A

  • Injectable hydrogel system of combining chemotherapy with photothermal therapy and preparation thereof

    CN111728938A

  • Injectable photo-thermal chemotherapy sensitization drug-loaded hydrogel and preparation method thereof

    CN112972366A

  • Gold composite copper selenide nanoparticle and preparation method and application thereof

    CN114533868A